A Computational Study on the Performance Improvement of Low-Speed Axial Flow Fans with Microplates - D. Luo; D. Huang; X. Sun; X. Chen; Z. Zheng (Journal of Applied Fluid Mechanics, 2017)
This paper proposes the use of microplates as a new flow control device to suppress boundary layer separation on blades and thus improve the aerodynamic performance of a low-speed axial flow fan. A computational study is performed by means of computational fluid dynamics (CFD) simulations. Numerical investigations are carried out based on Reynolds-averaged Navier-Stokes (RANS) method. The shear stress transport (SST) turbulence model and high-quality computational grids are adopted for CFD simulations. An exhaustive comparison of the fans with and without control has been conducted in terms of characteristic curves, streamlines and pressure distributions. The purpose of this work is to better understand the underlying flow control mechanisms of microplates. It is found that the total efficiency is slightly lowered when the controlled fan operates at the design flow rate. However, as the flow rate changes, the total efficiency of the controlled fan varies more gently than the original fan without control. Traced streamlines show that flow separation on blade surfaces is effectively controlled and radial flow migration on the suction surface is evidently diminished. Numerical results indicate that microplates significantly alleviate fan stall and have considerable beneficial effects on fan performance.